Entrepreneurship Business Plan_ N14T17_Times in the City_4259211 - Seelam, Kranthi Rekha (2016)
Times in the city, is an Indian based English newspaper company which began in Sept. 2015 which is intended for weekly publication. It covers major events in and around Kakinada city, with sections on local news, sports news, business news and political news. This report identifies the ways in which the independent free-circulation community newspaper in India can achieve significant growth in their advertising revenues. The content of the newspaper is systematically related to the community situations and the weekly events in the city in various industries. Times in the city will be owned and managed by Md.Valli Basha, who has experience in diverse businesses such as software and retail.